EMBRAPA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
The Brazilian Agro-pastoral Research Company, EMBRAPA, was set up on 26 April 1973. The company possesses modern laboratories and research stations and is organised into two departments and 37 Research Units , which are situated in very diverse...